2014
DOI: 10.1164/rccm.201403-0483oc
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Influence of Endogenous Estrogen in Pulmonary Hypertension

Abstract: Rationale: The incidence of pulmonary arterial hypertension is greater in women, suggesting estrogens may play a role in the disease pathogenesis. Experimentally, in males, exogenously administered estrogen can protect against pulmonary hypertension (PH). However, in models that display female susceptibility, estrogens may play a causative role.Objectives: To clarify the influence of endogenous estrogen and sex in PH and assess the therapeutic potential of a clinically available aromatase inhibitor. Methods:We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
187
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 133 publications
(197 citation statements)
references
References 32 publications
8
187
1
1
Order By: Relevance
“…Preclinical and clinical studies implicate aromatase as a potential contributor to PAH pathogenesis [6,9]. Similarly, oestrogen receptor-mediated signalling has been linked to PAH development [8].…”
Section: @Erspublicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Preclinical and clinical studies implicate aromatase as a potential contributor to PAH pathogenesis [6,9]. Similarly, oestrogen receptor-mediated signalling has been linked to PAH development [8].…”
Section: @Erspublicationsmentioning
confidence: 99%
“…Oestrogen effects are therefore highly context and compartment specific. For example, E2 has been shown to stimulate pulmonary artery smooth muscle cell proliferation but to exert anti-proliferative effects in pulmonary artery endothelial cells [6][7][8]31]. Similarly, in a recent microarray analysis of lungs from chronically hypoxic rats treated with E2, the E2-regulated genome indicated that E2 regulates multiple genes whose activation or inhibition is consistent with anti-proliferative effects, but that E2 also induces changes consistent with pro-proliferative or pro-angiogenic effects [32].…”
mentioning
confidence: 99%
See 3 more Smart Citations